2012
DOI: 10.1037/a0025907
|View full text |Cite
|
Sign up to set email alerts
|

Children discard a resource to avoid inequity.

Abstract: Elucidating how inequity aversion (a tendency to dislike and correct unequal outcomes) functions as one develops is important to understanding more complex fairness considerations in adulthood. Although previous research has demonstrated that adults and children reduce inequity, it is unclear if people are actually responding negatively to inequity or if people dislike others getting more than them (motivated by social comparison) and like to share maximal resources, especially with those who have few resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
322
2
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 324 publications
(358 citation statements)
references
References 102 publications
(164 reference statements)
26
322
2
8
Order By: Relevance
“…This is inconsistent with literature which suggests older children discard resources in order to be fair (Shaw & Olson, 2012). However, it was revealed that children were becoming more equitable over time, exhibiting less bias with more trials.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…This is inconsistent with literature which suggests older children discard resources in order to be fair (Shaw & Olson, 2012). However, it was revealed that children were becoming more equitable over time, exhibiting less bias with more trials.…”
Section: Discussioncontrasting
confidence: 56%
“…Furthermore, based upon prior literature on social preferences (Kinzler et al, 2009), when race and accent are pitted against one another (i.e., presented incongruently), children are expected to give more resources to their accent ingroup over their race in-group. Finally, older children are expected to discard a resource and favour fairness and therefore be less influenced by in-group bias (Shaw & Olson, 2012).…”
Section: The Current Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies report different results depending on the context in which children are observed, the role of adults in the process, and the alternatives children have at their disposal in the test situation. Most straightforward, in thirdparty situations where they must distribute resources among others, children from as young as 3 years show a very strong bias for equal distributions (e.g., Frydman & Bryant, 1988;Olson & Spelke, 2008;Peterson, Peterson, & McDonald, 1975;Rochat et al, 2009;Shaw & Olson, 2012). When young children themselves are among the recipients, however, the situation becomes more complicated.…”
Section: Introductionmentioning
confidence: 99%